2016
DOI: 10.1074/jbc.m116.720284
|View full text |Cite
|
Sign up to set email alerts
|

Lipids Regulate Lck Protein Activity through Their Interactions with the Lck Src Homology 2 Domain

Abstract: Lymphocyte-specific protein-tyrosine kinase (Lck) plays an essential role in T cell receptor (TCR) signaling and T cell development, but its activation mechanism is not fully understood. To explore the possibility that plasma membrane (PM) lipids control TCR signaling activities of Lck, we measured the membrane binding properties of its regulatory Src homology 2 (SH2) and Src homology 3 domains. The Lck SH2 domain binds anionic PM lipids with high affinity but with low specificity. Electrostatic potential calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 57 publications
11
48
0
Order By: Relevance
“…Recent studies revealing that the activation of TCR upon the dynamic 2D binding with pMHC in physiological conditions is likely to occur through mechanisms that are quite different from those observed when the receptor is stimulated by antibody crosslinking 54 , 55 . On the other hand, the differential effects of MCID expression on the pMHC- and soluble anti-CD3-elicited TCR activation suggests that these effects are not due to TCR-unrelated alterations such as a higher Lck activity 56 or positive feedback effects from down-stream signaling events such as a stronger calcium influx 10 . Additionally, in our opinion, the effects of the phosphatase on TCR activation were not due to diminished cell contacts, owing to results from a previous study that showed that the reduction of PI(4,5)P2 levels in T cells promotes rather than inhibits the contacts between T cells and APCs 57 , which could be a result of decreased T cell membrane rigidity 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealing that the activation of TCR upon the dynamic 2D binding with pMHC in physiological conditions is likely to occur through mechanisms that are quite different from those observed when the receptor is stimulated by antibody crosslinking 54 , 55 . On the other hand, the differential effects of MCID expression on the pMHC- and soluble anti-CD3-elicited TCR activation suggests that these effects are not due to TCR-unrelated alterations such as a higher Lck activity 56 or positive feedback effects from down-stream signaling events such as a stronger calcium influx 10 . Additionally, in our opinion, the effects of the phosphatase on TCR activation were not due to diminished cell contacts, owing to results from a previous study that showed that the reduction of PI(4,5)P2 levels in T cells promotes rather than inhibits the contacts between T cells and APCs 57 , which could be a result of decreased T cell membrane rigidity 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the SH2 domain of Lck can also interact with lipid within the plasma membrane upon TCR activation. This binding might be crucial for a lateral diffusion of Lck to interact with the triggered TCR–CD3 complex . These data indicate that localization of Lck to TCR–CD3s that are phosphorylated on few tyrosines facilitates the phosphorylation of the other ITAM tyrosines within CD3.…”
Section: Lckmentioning
confidence: 80%
“…An indirect interaction might be mediated by RhoH, a haematopoietic‐specific Rho GTPase . The direct interaction might be mediated by the SH2 domain of Lck and phosphorylated ITAMs . In addition, the SH2 domain of Lck can also interact with lipid within the plasma membrane upon TCR activation.…”
Section: Lckmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is relatively well documented that the conformational states control enzymatic activity, how membrane-bound Lck finds and phosphorylates its substrates is not well understood. For example, the link between phosphorylation state and activity is well established 39 , as well as some interactions of Lck with other proteins 40-43 and lipids 44 Most studies so far have focused on whether or not T cell stimulation results in an ‘activation’ of Lck itself, i.e., whether there is an overall increase of Lck molecules in the open conformation and whether a stable pool of open Lck already exists in resting T cells. However, it is also possible that in the dynamic environment of the inner leaflet of the plasma membrane, Lck switches between open and closed states, as many other types of enzymes do 45-47 .…”
Section: Discussionmentioning
confidence: 99%